Transmission line failure propagation under extreme wind scenarios: extratropical cyclones. (1st June 2023) - Alminhana, Fabio; Mason, Matthew; Albermani, Faris
Abstract: Catastrophic transmission line cascades can occur during severe storm scenarios and pose a serious threat to the power industry. This article describes an event-based approach devised to numerically simulate synoptic wind fields caused by extratropical cyclones impacting a line segment. Correlated time-dependent wind speeds are produced at selected points along the line section according to the wind field characteristics. The accuracy of the wind field produced by the method is verified by comparing the statistical properties of simulated wind records with respective theoretical values. The wind velocity time histories are converted into wind loads and used in a special-purpose nonlinear dynamic analysis technique, which models multi-span line sections under progressive failure. A vectorial version of the procedure provided by the standard IEC 60826 is used to generate wind loads based on the simulated speeds. A case study investigating the response of an existing 230 kV single-circuit line section to two extratropical cyclone wind fields with different intensities is presented. Highlights: Time-domain dynamic analysis can predict TL progressive failures under extreme winds. ARMA generates accurate wind turbulence for suitable time increments and ARMA orders. Relevant across-wind response in TL supports occurs during extratropical cyclones.